Public enforcement through independent directors - Li, Xiaoxi; Rao, Pingui; Yang, Yong George; Yue, Heng (Contemporary Accounting Research, 2024)
Abstract We examine how public enforcement and private enforcement interact to contain self‐dealing activities in emerging markets. Using data from China, we find that firms receiving comment letters concerning related party transactions (RPTs) from stock exchanges significantly reduce their RPTs in subsequent years. We further find that (1) the subsequent reduction in RPTs is more pronounced when independent directors have higher career or reputation concerns and (2) independent directors are more likely to dissent or resign if their firms do not significantly reduce RPTs after receiving RPT comment letters, especially if they have high reputation concerns. Our study sheds light on a within‐firm mechanism through which public enforcement takes effect. Our empirical findings also illustrate how “sunshine enforcement”—maintaining timely transparency of the enforcement process—can significantly enhance the effectiveness of regulatory programs.